2020
DOI: 10.1177/1464420720943537
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation, statistical modeling and multi-objective optimization of creep age forming of fiber metal laminates

Abstract: The experimental assessment of the creep age forming performance of fiber metal laminates was considered in this study. To this end, different fiber metal laminates with the stacking sequence of [Al/02/Al] were manufactured using aluminum alloy 6061 sheets as skins along with E-glass fiber-reinforced polypropylene and E-glass fiber-reinforced polyamide 6 as two different cores. Next, a comprehensive investigation was conducted on the impacts of two main parameters in the creep forming process, i.e. the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…122 Later, this technique was applied to fiber reinforced metal laminates. For example, Safari et al 123 carried out a systematic experimental study on the creep age-forming properties of fiber/metal laminates. The results showed that with an increase in either time or temperature, the spring-backs of fiber/metal laminates decreased due to the decrease in elastic strains and the increase of creep strains during the two types of creep age process.…”
Section: Hot-sizingmentioning
confidence: 99%
“…122 Later, this technique was applied to fiber reinforced metal laminates. For example, Safari et al 123 carried out a systematic experimental study on the creep age-forming properties of fiber/metal laminates. The results showed that with an increase in either time or temperature, the spring-backs of fiber/metal laminates decreased due to the decrease in elastic strains and the increase of creep strains during the two types of creep age process.…”
Section: Hot-sizingmentioning
confidence: 99%
“…Glass production has evolved over thousands of years to be ubiquitously used in recent decades in packaging containers due to favorable properties in that format (Flood et al, 2020). Glass is an excellent recyclable material that can be processed for use in new manufactured forms (Safari et al, 2020).…”
Section: Problem Descriptionmentioning
confidence: 99%
“…There are many common face sheet types for composite sandwich panels [5][6][7][8][9][10], e.g., wood materials, metal materials, fiber reinforced plastics composite materials, etc. In recent years, a new face sheet, fiber metal laminate (FML), which combines the performance advantages of metal alloy and composite materials, has attracted much attention due to its excellent impact resistance and high specific strength/stiffness [11][12][13][14]. Many researchers have recently focused on the mechanical properties of composite sandwich structures with FML face sheets [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%